Improving Pancasila Education Learning Outcomes Using the Problem Based Learning Method for Class V.III B Students at UPT SMPN 6 Pangsid Sidenreng Rappang Regency - Heril Heril; Harfiani Harfiani; Nur Asizah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to apply the Problem Based Learning (PBL) model to find out how students' learning outcomes improve in Pancasila Education lessons in class VIII.B at UPT SMPN 6 Pangsid, Sidenreng Rappang Regency.This research is a type of Classroom Action Research (CAR). The subjects in this research are all students of class VIII.B at UPT SMPN 6 Pangsid, and the object of the research is the improvement of student learning outcomes. The data collection techniques used in this study are observation and learning outcome tests, and the data analysis technique uses a quantitative descriptive method. From the research findings, the application of the Problem Based Learning (PBL) model in class VIII.B at UPT SMPN 6 Pangsid, Sidenreng Rappang Regency, can improve students' learning outcomes. In the pre-cycle, student learning activity showed that only 45% of students met the set standards with an average score of 73.25. However, after implementing Problem Based Learning (PBL) in the first cycle, students' learning activity increased to 85% with an average score of 78.5. In the second cycle, it increased again to 95% with an average student score of 82.75.